2013
DOI: 10.1111/pbr.12127
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a major QTL for adult plant resistance to coffee leaf rust (Hemileia vastatrix) in the natural Timor hybrid (Coffea arabica x C. canephora)

Abstract: Most of the commercial varieties of coffee (Coffea arabica L.) derived from the Timor hybrid (TH) have been shown to contain major genes for coffee leaf rust (CLR) resistance. To identify markers tightly linked to such genes, an F2 mapping population derived from a cross between ‘Caturra’ (susceptible variety) and the TH‐derived DI.200 line (highly resistant) was generated. Using expressed sequence information and a bioinformatics approach, both targeted region amplified polymorphism (TRAPs) markers and simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…Brito et al (2010) reported one dominant gene conditioning the resistance of HDT UFV427-15 to race II. Romero et al (2014) reported one QTL region corresponding to a new and genetically independent S H gene of DI200, a line derived from Caturra×HDT CIFC1343, using a mix of uredospores of H. vastatrix field collected from Caturra cultivar.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brito et al (2010) reported one dominant gene conditioning the resistance of HDT UFV427-15 to race II. Romero et al (2014) reported one QTL region corresponding to a new and genetically independent S H gene of DI200, a line derived from Caturra×HDT CIFC1343, using a mix of uredospores of H. vastatrix field collected from Caturra cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…C. arabica is a source of S H 1, S H 2, S H 4, and S H 5; Coffea liberica of S H 3; and C. canephora of S H 6, S H 7, S H 8, and S H 9 (Wagner and Bettencourt 1965;Noronha-Wagner and Bettencourt 1967;Bettencourt and Carvalho 1968;Bettencourt and Noronha-Wagner 1971;Bettencourt et al Communicated by D. Grattapaglia This article is part of the Topical Collection on Disease Resistance 1980; Bettencourt and Rodrigues 1988). Other major and minor genes of C. canephora may condition coffee leaf rust (CLR) resistance (Rodrigues et al 1975;Eskes and Da Costa 1983;Bettencourt and Rodrigues 1988;Eskes et al 1990; Várzea and Marques 2005;Herrera et al 2009;Romero et al 2010Romero et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BE5 Wush-Wush access originates from Ethiopia, with the SH1 resistance factor (Rodrigues, Braghini and Guerreiro Filho, 2017) and has red fruits with early and uniform ripeness. The Híbrido de Timor genotype comes from the interspecific crossing of C. arabica and C. canephora and the descendants of this genotype are widely used in genetic improvement to promote resistance to various coffee diseases (Setotaw et al, 2010;Romero et al, 2014). In addition to being resistant to coffee tree diseases, several studies confirm that the Híbrido de Timor germplasm can be used as a source of genes to improve other characteristics of interest, such as coffee beverage.…”
Section: Multivariate Data Analysismentioning
confidence: 99%
“…The cultivars descended from the Timor Hybrid offered resistance to Race II, and for a time it did succeed in lowering the occurrences of outbreak of the fungus. However recently it has been found that CLR races are adapting as well, and coffee varieties that were resistant are now susceptible to the disease due to new races becoming prominent (Romero et al, 2014). Further work has been done to understand the pathogenicity of CLR along with researching how new races develop so quickly as to make resistant cultivars null and void.…”
mentioning
confidence: 99%